The Role of Cytochrome P450 AbyV in the Final Stages of Abyssomicin C Biosynthesis. Issue 3 (8th December 2022) - Devine, Andrew J.; Parnell, Alice E.; Back, Catherine R.; Lees, Nicholas R.; Johns, Samuel T.; Zulkepli, Ainul Z.; Barringer, Rob; Zorn, Katja; Stach, James E. M.; Crump, Matthew P.; Hayes, Martin A.; van der Kamp, Marc W.; et al.
Abstract: Abyssomicin C and its atropisomer are potent inhibitors of bacterial folate metabolism. They possess complex polycyclic structures, and their biosynthesis has been shown to involve several unusual enzymatic transformations. Using a combination of synthesis and in vitro assays we reveal that AbyV, a cytochrome P450 enzyme from the aby gene cluster, catalyses a key late‐stage epoxidation required for the installation of the characteristic ether‐bridged core of abyssomicin C. The X‐ray crystal structure of AbyV has been determined, which in combination with molecular dynamics simulations provides a structural framework for our functional data. This work demonstrates the power of combining selective carbon‐13 labelling with NMR spectroscopy as a sensitive tool to interrogate enzyme‐catalysed reactions in vitro with no need for purification. Abstract : The cytochrome P450 enzyme AbyV catalyses a key epoxidation in the final stages of the biosynthesis of the spirotetronate antibiotic abyssomicin C. Combining structural and computational data with a 13 C labelling strategy was found to be a powerful approach to interrogate the biotransformation and determine the precise function of the enzyme.